Analisis Kontribusi Sektor Pariwisata terhadap Peningkatan Produk Domestik Regional Bruto (PDRB) Provinsi Jawa Barat - Ainur Ridho Hafied (CV. Ulil Albab Corp, 2026)
Each region has its own leading sector that significantly contributes to its Gross Regional Domestic Product (GRDP). This study aims to examine whether the tourism sector is considered a leading sector and its contribution to the GRDP in West Java Province. The research uses GRDP by industry data from West Java Province and National Gross Domestic Product (GDP) by industry, employing the Location Quotient (LQ), Shift Share, and Panel Least Squares (PLS) methods. The analysis shows that the tourism sector in West Java is not a leading sector despite the abundance of tourist destinations in the province. This raises the question of why the tourism sector, despite its potential, does not emerge as a key driver of economic growth. Therefore, this study seeks to provide valuable insights for policymakers to transform the supporting businesses in the tourism sector into a leading sector by leveraging the existing resources and enhancing its contribution to the regional economy.